Asymptomatic adult type IV sacrococcygeal teratoma: incidental diagnosis in a case of subfertility - Daksha, Shraddha; Khanna, Shakti Bhan; Dash, Kiranabala; Zaidi, Shuaib; Kashyap, Vikas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Sacrococcygeal teratomas (SCT) are rare congenital tumours that are even more uncommon when present in adulthood. They are derived from residual stem cells in the presacral space that differentiate into clusters of somatic cells. We present a case of asymptomatic sacrococcygeal teratoma (SCT) in 28 years old female, presented for subfertility workup and diagnosed incidentally while investigating for it. Preoperative diagnosis was complex cystic lesion involving presacral space with possibility of dermoid, epidermal, or cystic presacral hamartoma. The mass was completely excised through abdomen and sacral approach. Histopathology confirmed it to be sacrococcygeal teratoma. Although rare, saccrococcygeal teratoma (SCT) should be considered in differential diagnosis of presacral masses in adult female. Complete surgical excision remains the cornerstone of treatment with the involvement of multidisciplinary approach.